Kura e tai aniwhaniwha (schools and tsunami): Bi-cultural and studentcentred tsunami education in aotearoa New Zealand - Kaiser L; Boersen K (Australian Institute for Disaster Resilience, 2020)
Recent events in Aotearoa New Zealand, such as the Canterbury earthquakes in 2010 and 2011 and the Kaikōura earthquake in 2016, highlight the need for comprehensive and inclusive disaster education programs that are geographically and contextually relevant. Disaster risk reduction activities in Aotearoa New Zealand have historically adopted a top-down, expert-driven approach. They have also employed relatively homogenous methods for how communities in New Zealand can prepare for and respond to disasters. As a result, the inclusion of Māori communities and voices within traditional disaster risk reduction planning has been sparse. In addition, there is a lack of preparedness materials for tsunami designed specifically by Māori with Māori community needs front and centre. This paper documents a pilot education project taking an inclusive approach to increasing the knowledge and preparedness of tamariki (children) and rangatahi (youth) in coastal areas of Aotearoa New Zealand that are vulnerable to tsunami. Research was undertaken to develop a toolkit with kura kaupapa Māori (Māori-language immersion schools) and schools located in tsunami evacuation zones in Hawke’s Bay, on the east coast of the North Island. A Māori-led, bi-cultural approach to developing and running the activities was taken. The aim was to create culturally and locally relevant materials for ākonga (students) and kura kaupapa Māori as well as giving ākonga a proactive role in making their communities better prepared for a tsunami event.